Role of estrogen nuclear receptor (ER) in T helper cells - Mohammad, Imran (2015)
Multiple studies have demonstrated that estrogen (17β Estradiol) affects innate and adaptive immune systems. Its role as protective factor has been implicated in autoimmune diseases such as multiple sclerosis, rheumatoid arthritis and systemic lupus erythematosus. Estrogen exerts its action on immune cells using estrogen nuclear receptors, estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ). T helper (Th) cells are key regulators of the adaptive immune system. However, the mechanism how estrogen regulates T helper subset cells is still uncertain. To study the effect of estrogen and molecular mechanism, I silenced the estrogen alpha receptor gene that is predominantly expressed in T cells, by using siRNA approach. I observed that knock down of ERα is affecting Th1 by elevating T-bet, Th2 by increasing GATA3 and Treg by reducing Foxp3 levels. The outcome of this thesis will help in understanding pathophysiological effects of T helper cells and also the role of estrogen receptors in T cells and their effects in cancer immunity and autoimmunity.